E-Gestión documental: lineas de trabajo para su implementación - Sierra Escobar, Luis Fernando
In recent years, the subject of electronic archival documents has taken a big rise for the proper management and administration of information in public and private entities. Therefore, the present article describes the main lines of work for implementaing an e- document management policy from an archival perspective, leveraged in international authors key speeches, and the good practices of students taking a technological specialization who participated in the present study.The research methodology was based on the qualitative approach, with the use of participant observation as a research strategy, articulated with the competences, activities and learning outcomes proposed in the training project “Management of electronic documents in public and entities”, developed in the framework of the research.Finally, the results of the research showed two categories: one related to the contextualizing documentary e-management and its links and determinants: e- administration, electronic records management system (ERMS) and digital preservation; and another category related to the lines of work for its implementation: line 1: e-document management in the absence of an ERMS; line 2: parameterization of an ERMS, based on documentary planning, and line 3: longterm preservation of electronic archive documents.